CONFLICT MANAGEMENT STYLES OF WOMAN SCHOOL PRINCIPAL: A STUDY IN A PRIVATE SCHOOL OF PALEMBANG - Ahmad Zainudin; Monalisa Monalisa (Global Expert: Jurnal Bahasa dan Sastra, 2022)
This study investigated the most dominant conflict management style applied by woman school principal in one private high school in Palembang. The mixed-method research was applied, 18 teachers and one woman principal in this school were selected as the participants of this study. A 28-itemquestionnairewas distributed in order to measure the teachers’ opinions towards their principal conflict management style with teacher-relationship and interviewschedule-face to face was constructed to the principal to get deeper information. Results reveal that this woman school principal demonstrates integrating style which is considerate enough to high concern both for self and for others teachers.